Bell’s Palsy: Diagnosis dan Tata Laksana - Zanty Rakhmania Putri (Cermin Dunia Kedokteran, 2022)
Bell’s palsy merupakan gangguan saraf akut pada wajah dengan ciri kelemahan wajah unilateral dan tanpa penyebab pasti. Kelemahan wajah dapat berupa berkurangnya kerutan dahi, sulit menutup mata, kelemahan sudut bibir, hilangnya sensasi pengecapan, dan gejala lainnya berdasarkan cabang saraf wajah yang terkena. Diagnosis melalui anamnesis dan pemeriksaan klinis. Pemeriksaan penunjang untuk menilai faktor risiko dan menyingkirkan diagnosis lain. Pengobatan dapat secara non-farmakologis dan farmakologis. Bell’s palsy is an acute facial nerve disorder with unilateral facial weakness without definite cause. The disease may manifest as diminished forehead wrinkles, difficulty to close lid, weakness at the corner of the lips, loss of taste sensation, and other symptoms based on affected facial nerve branch. Diagnosis can be made through anamnesis and clinical examination. Additional examinations can evaluate risk factors and eliminate other diseases. Treatment can be non-pharmacological and pharmacological.